Types and Health Hazards of Fibrous Materials Used as Asbestos Substitutes - Seung-Hyun Park (Elsevier, 2018)
Asbestos has been banned in many countries but many countries, including developing countries, are still using asbestos or materials containing asbestos. Substitute materials have been studied and developed over a long period of time because of the hazards of asbestos, and many people have recently shown interest in the hazards of substitute materials. However, comprehensive information about the types of asbestos substitutes, their use and health hazards, and references for the protection for the health of workers is limited. The purpose of this study is to provide people in the related industries with information on the types and health hazards of fibrous materials that can be used as asbestos substitutes. According to the patent resources from the United States and Europe, fibrous materials have been used to develop asbestos-free products since before 1980. Recently, the health hazards of asbestos substitutes have been assessed and many additional researches are required. However, only some of the substitute materials have been assessed for health hazards, and health hazard data has not been sufficient in many cases. Therefore, efforts should be made to minimize workers' exposure to substitute materials that do not contain asbestos. Keywords: Asbestos, Asbestos-free products, Asbestos substitutes, Fibrous materials